Convents and Nuns in Eighteenth-Century French Politics and Culture - Choudhury, Mita, 1964- (Book collections on Project MUSE., 2004)
Mita Choudhury explores the place of the nunnery & of nuns in French society during the 18th century, examining the long struggle to escape the dominance of male clergy & then the increasing pressure on their very existence in the years leading up to & during the Revolution.